Analisis Spasial Pengembangan Kawasan Air Terjun Janji Kabupaten Humbang Hasundutan - Darmanto Silaban; Achmad Siddik Thoha; Muhammad Taufiq (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Spatial-based tourism development planning can help various parties to develop tourism in Lake Toba, especially in villages in Humbang Hasundutan Regency. The purpose of this research is to spatially analyse the physical characteristics and level of suitability of Janji Waterfall tourism development to support tourism development plans. The data used in this study are administrative boundary maps, soil type maps, land cover maps, slope maps, coordinates of the location of attractions and tourism facilities. Spatial analysis using Geographic Information System tools with join-space and overlay methods were used to describe the physical characteristics of the area, accessibility conditions, tourism facilities conditions and the level of suitability for tourism development. Based on the physical characteristics of the area, Janji Waterfall has supporting aspects in the form of beautiful natural scenery in the form of water flow, hills, vegetation and lakes. Accessibility to the tourism areas is easy from different locations as good quality road access already exists. Many support facilities are built in flat areas and close to settlements. The site or location of the waterfall is mostly in the criteria for the suitability of the development area, which is quite suitable and very suitable. For future development plans, it is recommended that managers, village governments and local governments work together. Visitor safety needs attention as the potential danger of landslides and flash floods is a threat that needs to be anticipated.